2010
DOI: 10.1007/s00431-010-1169-8
|View full text |Cite
|
Sign up to set email alerts
|

Sleep habits and sleep disturbances in Dutch children: a population-based study

Abstract: Sleep disorders can lead to significant morbidity. Information on sleep in healthy children is necessary to evaluate sleep disorders in clinical practice, but data from different societies cannot be simply generalized. The aims of this study were to (1) assess the prevalence of sleep disturbances in Dutch healthy children, (2) describe sleep habits and problems in this population, (3) collect Dutch norm data for future reference, and (4) compare sleep in children from different cultural backgrounds. A populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
94
8
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(111 citation statements)
references
References 31 publications
(52 reference statements)
8
94
8
1
Order By: Relevance
“…The Dutch Children Sleep Habits Questionnaire (CSHQ), Adolescent Sleep Habits Questionnaire (ASHQ), and the Sleep Self‐Report (SSR) were used to assess child sleep . Scores of healthy Dutch children are available . Only (sub)scales with an acceptable internal consistency (Cronbach's alpha ≥0.60) in both the study population and in healthy children are reported here.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Dutch Children Sleep Habits Questionnaire (CSHQ), Adolescent Sleep Habits Questionnaire (ASHQ), and the Sleep Self‐Report (SSR) were used to assess child sleep . Scores of healthy Dutch children are available . Only (sub)scales with an acceptable internal consistency (Cronbach's alpha ≥0.60) in both the study population and in healthy children are reported here.…”
Section: Methodsmentioning
confidence: 99%
“…Recall period was the last week for all child sleep questionnaires and higher scores were indicative of more sleep problems. Missing items were imputed as item means of the population if less than half of the items on a scale were missing …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sharing rates are low in Western countries . A total of 27% shared a room in the USA, 14.6% in China, 17% in Spain, and 31.4% in Belgium, while prevalence of bed sharing in the USA, China and Belgium were 11%, 23% and 3.6%, respectively. Li et al .…”
Section: Discussionmentioning
confidence: 96%